Analysis of The Management Functions of Sports Organizations - Ahmad Yani; Toktong Parulian; Yola Yolanda (Universitas PGRI Palembang, 2023)
This study aims to determine the management function of sports organizations in the Management of the Bono River Community (BRC) of Meranti Bay. Information mining is obtained through a qualitative descriptive approach with structured interview data collection techniques with tools in the form of interview guidelines, notebooks, and documentation. The research data processing stage is carried out by means of data reduction, data presentation and data verification. Analysis of management functions is the result of a way of solving problems through the process of planning, organizing, mobilizing, supervising, and assessing to obtain the desired results. To eliminate differences in the construction of reality that exist in the context of a study while collecting data on events and relationships from different views, researchers used source triangulation techniques. The results of this study show that the analysis of the management function of sports organizations in the Meranti Bay Bono River Community (BRC) Management is considered ineffective.